POLA KOMUNIKASI PASANGAN SUAMI ISTRI DALAM TEKANAN PASCA MELAHIRKAN DI KOTA BANDAR LAMPUNG - Kinantri Puspa Sari; Ramadhana, Maulana Rezi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
The postpartum period is a transitional period experienced by married couples who require adjustments to the presence of changes in their relationship, especially when the wife is experiencing postpartum stress (depression) during that period. The postpartum period causes changes in conditions followed by changing roles and responsibilities, which can affect the communication relationship between partners. This study focuses on communication patterns of married couples in postpartum pressure using the Interpersonal Communication Patterns Theory approach which is supported by the theory of relationship turbulence. The research method used is a qualitative method with data collection techniques in the form of interviews with four husband and wife couples who live in the city of Bandar Lampung, the determination of the informants is obtained through a snowball sampling strategy (multistage method) with expert informants as data confirmation. The results show that all couples have a separate balanced communication pattern (balanced split pattern) during the face of postpartum stress, which is marked by the division of responsibilities in different roles. In a balanced split communication pattern, all informants experience interferences as well as communication supports, and some experience relationship uncertainty, while constructive strategies are used as approaches in conflict management strategies between partners, characterized by open communication and negotiation. Conflicts related to childcare tasks and lack of quality interactions were the findings of this study. Abstrak Periode pasca melahirkan adalah periode transisi yang dialami oleh pasangan suami istri yang membutuhkan upaya penyesuaian dalam hubungan relasi, terlebih saat pihak istri mengalami tekanan/depresi pasca melahirkan selama periode tersebut. Periode pasca melahirkan menimbulkan perubahan kondisi, berupa perubahan peran dan tanggung jawab, yang dapat mempengaruhi hubungan komunikasi di antara pasangan. Penelitian ini berfokus pada pola komunikasi suami-istri dalam tekanan pasca melahirkan dengan metode penelitian kualitatif. Teknik pengambilan data berupa wawancara terhadap empat pasangan suami istri di Bandar Lampung yang didapat dari teknik pengambilan sample snowball sampling, Hasil menunjukkan bahwa seluruh pasangan memiliki pola komunikasi seimbang terpisah selama menghadapi tekanan pasca melahirkan, yang ditandai dengan adanya pembagian tanggung jawab pada peran yang berbeda. Dalam pola komunikasi seimbang terpisah, seluruh informan mengalami hambatan juga dukungan komunikasi, dan sebagian mengalami ketidakpastian hubungan. Sementara, strategi konstruktif digunakan sebagai pendekatan dalam strategi manajemen konflik di antara pasangan, ditandai dengan adanya keterbukaan komunikasi dan negosiasi. Konflik terkait dengan tugas pengasuhan anak dan kurangnya kualitas interaksi menjadi temuan dalam penelitian ini.